Original articleLow oxygen tension promotes redifferentiation of dedifferentiated human articular chondrocytes in vitro - Warnawin, Ewa; Burakowski, Tomasz; Gajewski, Michał; Kornatka, Anna; Rudnicka, Weronika; Michalak, Cezary; Małdyk, Paweł; Maśliński, Sławomir; Maśliński, Włodzimierz (Reumatologia/Rheumatology, 2006)
Articular cartilage degradation is a main cause of joint destruction in rheumatic diseases. An attractive possibility for cartilage repair is the use of cultured in vitro chondrocytes. However, cultured chondrocytes undergo dedifferentiation with loss of collagen II production, and increased synthesis of collagen I. Therefore, optimization of chondrocyte culture conditions in vitro is required. The aim of this work was to verify the hypothesis that chondrocytes cultured in vitro in conditions similar to their physiological environment: (1) fluctuating mechanical pressure, and/or (2) low oxygen tension, will express genes encoding extracellular matrix proteins characteristic for articular chondrocytes. To verify this hypothesis, chondrocytes isolated from cartilage of rheumatoid arthritis patients were cultured in normal (21%) or low (5%) oxygen tension, normal (1 atm) or increased (2 atm) in cyclic fashion, atmospheric pressure. The expression of genes characteristic for mature chondrocytes: aggrecan, collagen IIA and IIB, and gene present in dedifferentiated chondrocytes, collagen I, were analyzed in chondrocytes cultured in modified conditions. The results confirm that chondrocytes cultured in low (5%) oxygen tension, increased expression of mRNA encoding aggrecan, collagen IIA and IIB with simultaneous decrease of collagen I. No changes of cell morphology or proliferation rate were observed. Chondrocytes exposed to fluctuating pressure exert lower, but not significant extracellular matrix synthesis. Cells cultured in 5% O 2 exerted increased expression of mRNA encoding genes characteristic for differentiated chondrocytes i.e. aggrecan, collagen IIA and IIB, with simultaneous decreased expression of collagen I, a marker of dedifferentiated chondrocytes. These results suggest that low oxygen tension stimulates cultured chondrocytes toward functional redifferentiation of dedifferentiated chondrocytes. Mechanical stimulation is not required at this stage of culture.